Menjaga Ruang Siar Publik: Strategi KPID Jawa Timur dalam Menegakkan Nilai-Nilai Islam dan Budaya Lokal Melalui P3SPS - Kurrotul Hasanah Kurrotul Hasanah (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2025)
The Regional Indonesian Broadcasting Commission (KPID) of East Java is an independent institution responsible for ensuring that broadcasting institutions adhere to the Broadcasting Code of Conduct and the Broadcast Program Standards (P3SPS). This study aims to explain the strategies of KPID East Java in maintaining the public broadcasting space based on Islamic values and local cultural wisdom through the implementation of P3SPS principles. Using a qualitative descriptive method through in-depth interviews, observations, and documentation, the findings reveal that KPID’s monitoring strategy follows the PDCA (Plan–Do–Check–Act) quality management model integrated with Islamic ethical values and East Javanese cultural wisdom. This approach enables systematic and adaptive supervision in response to digital broadcasting developments while upholding public morality. Challenges remain, such as limited human resources and ineffective sanction regulations. The study highlights the importance of integrating Islamic values and local culture in broadcasting supervision to sustain a healthy and civilized public sphere